Cannabis and Associated Medicinal Herbs in Uganda - Lubogo, Isaac Christopher (Jescho Publishing House, 2022)
Cannabis is a drug plant. People use the dried leaves, seed oil, and other parts of the cannabis plant for recreational and medicinal purposes. It can have a pleasurable effect and may soothe the symptoms of various conditions, such as chronic pain. It is prudent to say that the first written record of the plant consumption and growing is in South Africa. Jan van Riebeeck, who ordered officers of the Voorman to purchase "daccha" in Natal for trade with the Khoikhoi. The Dutch East India Company attempted to establish a monopoly on its sale, and to that end prohibited cultivation of the plant by Cape settlers from 1680. However, the ready availability of cannabis in the wild and through trade with indigenous peoples meant that there was little profit to be made. Consequently, the prohibition was lifted in 1700. Beginning in 1860, the Natal Colony began to import Indian workers (called "coolies" at the time) to supplement their labour force. These Indians brought with them the habit of consuming cannabis and hashish, which blended with local, extant African traditions. The European authorities were concerned by this practice, believing it sapped the vitality of their workers; consequently, in 1870, Natal's Coolie Law Consolidation prohibited "the smoking, use, or possession by and the sale, barter, or gift to, any Coolies whatsoever, of any portion of the hemp plant (Cannabis sativa) ..."
A Discourse to Decriminalise and Delegalize
Keywords: Njaga (Cannabis); Legal Appraisal; Medicinal Herbs